2018
DOI: 10.4314/jfas.v9i5s.67
|View full text |Cite
|
Sign up to set email alerts
|

Mergers and acquisitions’s impact on financial performance: an evaluation with perspective of time

Abstract: Mergers and Acquisitions (M&A) is the most prefered technique of the corpoates from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Kinerja keuangan perusahaan yang semakin baik akan menjadikan perusahaan tersebut mempunyai daya saing yang tinggi sekaligus mampu untuk meningkatkan nilai perusahaan. Terdapat perbedaan hasil penelitian yang dilakukan oleh Tarigan et al (2018), Shrestha et al (2017), Lakhwani et al (2017), Yanan & Basit, (2016), Abdulazeez et al (2016), Saxena et al (2020), dan Yusuf & Ichsan, (2020) yang menunjukkan bahwa merger dan akuisisi dapat meningkatkan kinerja keuangan perusahaan. Sementara penelitian Sujud & Hachem (2018), Ahmed et al (2018) dan Shah & Khan (2017) yang menunjukkan hasil bahwa merger dan akuisisi tidak dapat meningkatkan kinerja keuangan perusahaan.…”
Section: Pendahuluanunclassified
“…Kinerja keuangan perusahaan yang semakin baik akan menjadikan perusahaan tersebut mempunyai daya saing yang tinggi sekaligus mampu untuk meningkatkan nilai perusahaan. Terdapat perbedaan hasil penelitian yang dilakukan oleh Tarigan et al (2018), Shrestha et al (2017), Lakhwani et al (2017), Yanan & Basit, (2016), Abdulazeez et al (2016), Saxena et al (2020), dan Yusuf & Ichsan, (2020) yang menunjukkan bahwa merger dan akuisisi dapat meningkatkan kinerja keuangan perusahaan. Sementara penelitian Sujud & Hachem (2018), Ahmed et al (2018) dan Shah & Khan (2017) yang menunjukkan hasil bahwa merger dan akuisisi tidak dapat meningkatkan kinerja keuangan perusahaan.…”
Section: Pendahuluanunclassified
“…In all over the world, M&A has become a prominent route to attain inorganic growth for corporations, but they must still choose targets to acquire or merge after cautious analysis of the costs and benefits associated with the M&A. An appropriate integration plan must be designed in advance to facilitate M&A (Lakhwani et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research was aimed at assessing the impact of the establishment of a state-owned holding company on the company performance in PT.X Group and to know whether the holding's objective to increase the company's financial performance after the establishment of the holding company is attained. Lakhwani et al (2017) conducted a research to 24 sample companies from various sectors in India that had acquired companies in the financial year of 20052006, to measure M&A financial performance in the long term with the support of Du Pont ROA Analysis and concluded that M&A was a good strategy for the long term and the company could gain optimal return provided that the selection of target is conducted wisely with a well-considered plan. M&A gained benefits in the long run but entirely depending on the company that selected this path and how to take it forward.…”
Section: Introductionmentioning
confidence: 99%
“…Tüm bu aşamalardan sonra, firmanın, birleşme/satın almanın gerçekleştirilme amacı doğrultusunda sinerji kurup kuramayacağına dair bir analiz yapması gerekmektedir. Eğer işlemler amacına ulaşmış ve sinerji yaratılmışsa elde edilen faydaların hemen bir etki mi yaratacağı yoksa şirketin finansal performanslarına yansımasının zaman mı alacağı incelenmelidir (Lakhwani, 2017).…”
unclassified